EVALUASI PENGGUNAAN ANTIHIPERTENSI TERHADAP MIKROALBUMINURIA DAN TERJADINYA STROKE BERULANG DI RSUD DUNGUS - Agustina, Hefida; Raising, Rahmawati; Harianto, Hendri; Perwirahayu Aji Saputri, Ika Sutra (Jurnal Ilmiah Bakti Farmasi, 2023)
Stroke or cerebrovascular injury is a loss of brain function caused by the cessation of blood supply to parts of the brain. Generally stroke occurs due to the culmination of cerebrovascular disease for several years. One way to prevent recurrent stroke is by using antihypertensive therapy to reduce high blood pressure. The purpose of this study was to describe the use of hypertension therapy for microalbuminuria and the incidence of recurrent stroke at Dungus Madiun General Hospital. This type of research used a descriptive observational design with a prospective method. Microalbuminuria laboratory results. Total data and samples were 7 patients